ISOLATION AND IDENTIFICATION OF MICROPLASTIC DEGRADING BACTERIA IN THE APHOTIC ZONE IN BAGANSIAPIAPI WATERS, RIAU - Bachar, Sutan; Feliatra, Feliatra; Nursyirwani, Nursyirwani (Asian Journal of Aquatic Sciences, 2025)
This study aims to isolate and identify microplastic-degrading bacteria from the aphotic zone in Bagansiapiapi waters, Riau Province. Seawater samples were taken from three different stations, namely the port area, the fisheries area, and the Rokan River estuary. Water quality parameters such as temperature, salinity, pH, current speed, brightness, and dissolved oxygen were measured to support environmental analysis. The method used in this study was a survey method, and the sampling location was around the Bagansiapiapi waters, Riau Province. A total of 9 samples were then taken to the laboratory for isolation and identification of microplastic-degrading bacteria. Bacterial isolation was carried out using Zobell Marine Agar media, morphological characterization and biochemical tests. The isolation results obtained 11 bacterial isolates with different morphological characteristics. The microplastic degradation test showed that three isolates, namely ISL1, ISL3, and ISL9, could degrade microplastics, with ISL1 showing a degradation percentage of 9.45%. Molecular analysis using 16S rRNA and BLAST techniques showed that the ISL1 isolate had a similarity of 99.93% with Stutzerimonas stutzeri. These results indicate the potential of native bacteria from the aphotic zone to be used in bioremediation efforts for microplastic pollution in waters